PENGARUH BRAND AWARENESS, BRAND EXPERIENCE, DAN BRAND PERSONALITY TERHADAP KEPUTUSAN PEMBELIAN DENGAN MINAT BELI SEBAGAI VARIABEL MEDIASI: Studi Empiris Kopi Janji Jiwa Magelang - Resmita , Nova; Ajeng Pramesti, Diesyana (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The purpose of this research is to see how brand awareness, experience with the brand, and brand personality influence purchasing decisions with purchase intention as a mediating variable. The general public who have purchased Kopi Janji Jiwa products are the subjects of this study. Using a purposive sampling method consisting of 105 respondents. Multiple linear regression was used in conjunction with the SPSS version 25.0 program. This study shows that purchasing interest is not influenced by brand awareness; Purchase interest is influenced by brand experience and brand personality; purchasing decisions are influenced by brand awareness; purchasing decisions are not influenced by brand experience and brand personality; and purchase interest does not mediate the influence of brand awareness, brand experience, and brand personality.